One Nation, Three Faiths: World War I and the Shaping of "Protestant-Catholic-Jewish" America. Issue 4 (13th November 2015) - Mislin, David
Abstract : During World War I, American political, military, and religious leaders sought to foster the view that protestants, Catholics, and Jews were equal stakeholders in society. Crucial in shaping the embrace of this "tri-faith" ideal were leading members of all three traditions, who used their connections to the federal government to ensure that many facets of national life reflected this new conception of the nation's religious character. The military chaplaincy put these ideals into practice, and interfaith activity became commonplace in the army. Protestant, Catholic, and Jewish chaplains worked closely together, and provided pastoral care or offered religious rites to wounded and dying soldiers from different faith traditions. This article examines how the wartime break from political and social normality, the desire to project a particular image of the nation abroad, and Americans' firsthand encounter with religion in Europe all contributed to idealizations of the inclusive nature of American civil religion during World War I. Yet, as this essay demonstrates, the transitional nature of wartime culture and the strong role of the federal government in fostering these values prevented this outlook from firmly taking root. The experience did, however, provide a critical precedent for subsequent idealizations of a protestant-Catholic-Jewish nation.